2012
DOI: 10.1051/0004-6361/201219604
|View full text |Cite
|
Sign up to set email alerts
|

An independent distance estimate to CW Leonis

Abstract: CW Leo has been observed six times between October 2009 and June 2012 with the SPIRE instrument on board the Herschel satellite. Variability has been detected in the flux emitted by the central star with a period of 639 ± 4 days, in good agreement with determinations in the literature. Variability is also detected in the bow shock around CW Leo that had previously been detected in the ultraviolet and Herschel PACS/SPIRE data. Although difficult to prove directly, our working hypothesis is that this variability… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
56
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 34 publications
6
56
0
Order By: Relevance
“…For some Galactic targets, large grains have proven necessary when near-IR visibility data are available, because they provide an additional scattering component. Examples include IRC +10 216 and OH 26.5, which were fitted with MoD code by Groenewegen et al (2012) and Groenewegen (2012), respectively. Recently, Norris et al (2012), Scicluna et al (2015), and Ohnaka et al (2016) found evidence for grains in the range 0.3-0.5 µm, and 0.1-1 µm grains are advocated to drive the outlow around oxygen-rich stars (Höfner 2008, Bladh & Höfner 2012).…”
Section: Dust Grain Propertiesmentioning
confidence: 99%
“…For some Galactic targets, large grains have proven necessary when near-IR visibility data are available, because they provide an additional scattering component. Examples include IRC +10 216 and OH 26.5, which were fitted with MoD code by Groenewegen et al (2012) and Groenewegen (2012), respectively. Recently, Norris et al (2012), Scicluna et al (2015), and Ohnaka et al (2016) found evidence for grains in the range 0.3-0.5 µm, and 0.1-1 µm grains are advocated to drive the outlow around oxygen-rich stars (Höfner 2008, Bladh & Höfner 2012).…”
Section: Dust Grain Propertiesmentioning
confidence: 99%
“…Combining several sparsely sampled epochs, they found that some lines of spatially extended species such as the SiCC and low-J CO lines showed little variation, while some other molecular lines such as high-J CO, CS, SiO, SiS, HCN, CCH N=6-5, and H 2 O lines all show evident variability. Particularly, the varying CCH N=6-5 line was argued to be emitted from an extended region in the CSE which, together with the far infrared (IR) variability of dust emission found by Groenewegen et al (2012), demonstrated the importance of IR excitation/heating of dust and gas in the outer parts of the CSE.…”
Section: Introductionmentioning
confidence: 96%
“…CW Leo (also known as IRC +10216) is the nearest carbon-rich asymptotic giant branch (AGB) star at a distance of about 120 to 150 pc (Men'shchikov et al 2001;Groenewegen et al 2012, and reference therein). During the AGB phase, the evolution is determined by mass loss, with the mass-loss rate being significantly higher than the rate at which mass is comsumed by nuclear burning (Lagadec et al 2008).…”
Section: Introductionmentioning
confidence: 99%